Towards an animal-centred ethics for Animal–Computer Interaction. Issue 98 (February 2017) - Mancini, Clara
Abstract: The emerging discipline of Animal–Computer Interaction (ACI) aims to take what in Interaction Design is known as a user-centred approach to the design of technology intended for animals, placing them at the centre of the design process as stakeholders, users, and contributors. However, current regulatory frameworks for the involvement of animals in research are not animal-centred, regarding them as research instruments, unable to consent to procedures that may harm them, rather than consenting research participants and design contributors. Such frameworks aim to minimise the impacts of research procedures on the welfare of individual animals, but this minimisation is subordinated to specific scientific and societal interests, and to the integrity of the procedures required to serve those interests. From this standpoint, the universally advocated principles of replacement, reduction and refinement aim to address the ethical conflicts arising from the assumed inability of individual animals to consent to potentially harmful procedures, but such principles in fact reflect a lack of individual centrality. This paper makes the case for moving beyond existing regulations and guidelines towards an animal-centred framework that can better support the development of ACI as a discipline. Firstly, recognising animal welfare as a fundamental requirement for users and research participants alike, the paper articulates the implications of a welfare-centred ethics framework . Secondly, recognising consent as an essential requirement of participation, the paper also defines criteria for obtaining animals׳ mediated and contingent consent to engaging with research procedures. Further, the paper argues for the methodological necessity, as well as the ethical desirability, of such an animal-centred framework, examining the boundaries of its applicability as well as the benefits of its application. Finally, the paper puts forward a series of practical principles for conducting ACI research, which imply but also essentially exceed the welfare and ethics requirements of current regulatory frameworks. Highlights: Propose an animal-centred ethical framework to support ACI development. Articulate the implications of a welfare-centred ethical approach. Define criteria for obtaining animals׳ mediated and contingent consent . Put forward a series of practical principles for conducting ACI research.